Intracellular antibody capture (IAC) methods for single domain antibodies. - Tanaka, T; Rabbitts, T (2012)
Intracellular single domain antibodies are recombinant proteins, comprising one variable region domain fragment, that bind specifically to intracellular molecules and can interfere with their particular functions within various cellular compartments. They are valuable tools in bioscience and potential macrodrugs in biotherapeutics; however, their application is still limited because of the difficulty and inefficiency of acquisition of functional intracellular antibodies. We describe here the new generation protocol for intracellular antibody capture to facilitate selection of functional single domains. This protocol uses a series of optimized single domain libraries, based on designed intracellular variable (VH or VL) region scaffolds, for direct in vivo isolation of single domains that bind to target proteins and interaction and for affinity maturation to develop sub-nM affinity antibody fragments. The method has advantages over other methods in that specific single domains are isolated directly within the reducing cellular environment and can be selected without in vitro antigen protein preparation.In an accompanying methods paper, we describe a simple extension of the methodology to isolate subsets of IAC-captured single domains that interfere with protein-protein interactions.